Ecosufism in Suluk Wujil: Harmony between God, Humans, and Nature in the Cosmology of Javanese Sufism - Abbas, Faiz Musthofa (KALAM, 2025)
The global ecological crisis cannot be adequately addressed solely through technological and economic solutions; it also requires the revival of spiritual awareness and environmental ethics. This article examines the concept of ecosufism in the Javanese mystical text Suluk Wujil, traditionally attributed to Sunan Bonang, by analyzing the depiction of the harmonious relationship between God, humans, and nature within the framework of Nusantara Islamic spirituality. This qualitative study employs a library research approach and is analyzed using Sufi hermeneutics and a Sufi cosmological perspective. The findings reveal that Suluk Wujil presents a cosmological framework integrating the metaphysical doctrine of waḥdat al-wujūd with Javanese cosmological concepts, particularly jagad ageng (macrocosm) and jagad alit (microcosm). This synthesis reflects a spiritual worldview in which nature is understood as a manifestation of divine presence rather than merely an object of exploitation. Furthermore, this study proposes the concept of “Ecosufistic Makrifat Epistemology,” suggesting that the attainment of makrifat involves not only inner spiritual transformation but also ecological awareness and ethical responsibility toward nature. Thus, Suluk Wujil offers a Nusantara ecosufism framework that provides a spiritual–ethical foundation for addressing contemporary ecological challenges.